Collecting qualitative data during a pandemic. (1st September 2021) - Silverman, David
Abstract : The claims of qualitative research are often based on being physically present in a setting and the ability that gives to record interactional features unavailable to quantitative research. In a medical context, this can involve a number of scenarios which include observing medical encounters or interviewing patients.The COVID-19 pandemic, however, has made such co-presence impractical. This short paper discusses ways around this problem. It also demonstrates that, in a digital age, being 'present' in the 'field' needs to be reconsidered.